2011
DOI: 10.1051/0004-6361/201016184
|View full text |Cite
|
Sign up to set email alerts
|

Differential adsorption of complex organic molecules isomers at interstellar ice surfaces

Abstract: Context. Over 20 of the ∼150 different species detected in the interstellar and circumstellar media have also been identified in icy environments. For most of the species observed so far in the interstellar medium (ISM), the most abundant isomer of a given generic chemical formula is the most stable one (minimum energy principle -MEP) with few exceptions such as, for example, CH 3 COOH/HCOOCH 3 and CH 3 CH 2 OH/CH 3 OCH 3 , whose formation is thought to occur on the icy mantles of interstellar grains. Aims. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 47 publications
7
63
1
Order By: Relevance
“…This concerted approach allows for determining values of adsorption energies, obtained with two independent methods, whose reliability is supported by thorough cross-checking between experiments and numerical simulations. The validity of such an approach has already been illustrated in the study of the adsorption of complex organic molecules on water ice (Lattelais et al 2011). In the present work, the adsorption of the two nitrile and isonitrile isomers has been studied on a silica surface, as a model for bare interstellar grain surface, and on a water ice surface, as water is the most abundant constituent of the icy mantles recovering the dust grains.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…This concerted approach allows for determining values of adsorption energies, obtained with two independent methods, whose reliability is supported by thorough cross-checking between experiments and numerical simulations. The validity of such an approach has already been illustrated in the study of the adsorption of complex organic molecules on water ice (Lattelais et al 2011). In the present work, the adsorption of the two nitrile and isonitrile isomers has been studied on a silica surface, as a model for bare interstellar grain surface, and on a water ice surface, as water is the most abundant constituent of the icy mantles recovering the dust grains.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…As periodic calculations were based on the replication of the unit cell along the three directions of space, the size of the unit cell is a critical parameter whose dimensions were determined here to avoid any spurious lateral and vertical interactions between successive slabs. The experience drawn from preceding studies (Lattelais et al 2011(Lattelais et al , 2015 showed that a distance of ∼14 Å between the adsorbed species is necessary to avoid the interactions generated by lateral translations. The energy minima were then obtained by full optimizations starting from most of the chemically reasonable positions (over atoms and depressions) and orientations of the adsorbates over the host surfaces.…”
Section: Theoretical Approach To Adsorption Energiesmentioning
confidence: 99%
“…Experimentally, the temperatures at which various species desorb from the ice have been characterized using the temperature programmed desorption (TPD) technique (see, e.g., Collings et al 2004). Recently, we reported a joint theory/TPD experiment (Lattelais et al 2011b) focused on the adsorption of two couples of isomers: acetic acid (AA)/methyl formate (MF) and ethanol (EtOH)/di-methyl ether (DME). Comparison between the theoretical adsorption energies E ads on ice with those derived from the TPD experiments showed that both agree whenever measurement is possible.…”
Section: Considered Grain Surfacesmentioning
confidence: 99%
“…A possible explanation for these exceptions is that adsorption on the grain surfaces plays a crucial role. In particular, Lattelais et al (2011b) carried out a study of the adsorption of the couple methyl formate and acetic acid and found that the relative adsorption energies may be at the origin of the exception to the MEP. Alternatively, isomerization by UV photolysis may have timescales that induce the observed MEP exception for the acetic acid -methyl formate couple (Puletti et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Here we address the question of how much the adsorption energy differs from one enantiomer to the other. To this end we rely on numerical simulations based on the methods of quantum chemistry, namely Density Functional Theory (DFT) that proved efficient in the super-molecule (cluster) and periodic approaches to this category of phenomena [4].…”
Section: Introductionmentioning
confidence: 99%